2018
DOI: 10.18488/journal.107.2018.61.20.31
|View full text |Cite
|
Sign up to set email alerts
|

Investment and Economic Growth: A Panel Data Analysis

Abstract: Article HistoryInvestment plays a vital part in economic progress of the countries. The current study tried to examine the influence of the investment on economic development of South Asian Association of Regional Cooperation (SAARC) countries by used the panel data for the dated 2000-2014. This study applied Hausman test to check the fixed effect model is appropriate or random effect model is appropriate. The empirical results explained that the random effect model is suitable in this study. Random effect mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 7 publications
3
5
0
Order By: Relevance
“…In other words, to achieve the high-performance record, nowadays, many organizations have been struggling to achieve organizational excellence so that they could differentiate themselves in the market from their rivals. Unfortunately, many of them failed to achieve this goal because of the lack of understanding of the business excellence concepts and processes (Dahlgaard, 2003;Riaz & Riaz, 2018;Aldulaimi, 2018). Moreover, although previous studies found benefits of adopting business excellence elements, most of these studies were in the USA and very few of these studies in the higher education sector of developing countries especially Palestine.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, to achieve the high-performance record, nowadays, many organizations have been struggling to achieve organizational excellence so that they could differentiate themselves in the market from their rivals. Unfortunately, many of them failed to achieve this goal because of the lack of understanding of the business excellence concepts and processes (Dahlgaard, 2003;Riaz & Riaz, 2018;Aldulaimi, 2018). Moreover, although previous studies found benefits of adopting business excellence elements, most of these studies were in the USA and very few of these studies in the higher education sector of developing countries especially Palestine.…”
Section: Introductionmentioning
confidence: 99%
“…While Zheng et al (2012) stated that consumers feel frustration because of the product purchased does not meet expectation which caused their self-esteem been loss. In result, the definition of psychological risk in this study as a possibility for consumers scares self-image and self-concept will be lost and the products may not suit for their image due to the product purchased (Asawa & Kumar, 2016;Riaz & Riaz 2018). Social risk can happen when individuals scare the product purchased may result in blameful ness from friends (Asawa & Kumar, 2016;Zheng et al, 2012;Singh, 2018).…”
Section: Literature Reviewmentioning
confidence: 96%
“…The findings suggest that U.S. financial shocks reverberate in advanced stock markets more strongly than shocks from other regions, including the Euro area and the United Kingdom. On the other hand,inward spillovers to the U.S. from advanced stock markets are minimal (Riaz & Riaz 2018). Bayoumi and Bui (2012) also finds two-way spillovers between the UK and Euro area financial markets (Razak, Sarpan & Ramlan 2018 Global Financial Crisis by using daily and weekly data from the following indices; S&P 500 Index for US, the FTSE Index for UK, the DAX for Germany, and Nikkei for Japan.…”
Section: Table 1 Correlation Of Weekly Leading Stock Marketsmentioning
confidence: 99%